Rotavirus activates a noncanonical ATM‐Chk2 branch of DNA damage response during infection to positively regulate viroplasm dynamics. (17th December 2019) - Sarkar, Rakesh; Patra, Upayan; Lo, Mahadeb; Mukherjee, Arpita; Biswas, Asim; Chawla‐Sarkar, Mamta
Abstract: Surveillance for maintaining genomic pristineness, a protective safeguard of great onco‐preventive significance, has been dedicated in eukaryotic cells to a highly conserved and synchronised signalling cascade called DNA damage response (DDR). Not surprisingly, foreign genetic elements like those of viruses are often potential targets of DDR. Viruses have evolved novel ways to subvert this genome vigilance by twisting canonical DDR to a skewed, noncanonical response through selective hijacking of some DDR components while antagonising the others. Though reported for many DNA and a few RNA viruses, potential implications of DDR have not been addressed yet in case of infection with rotavirus (RV), a double‐stranded RNA virus. In the present study, we aimed at the modulation of ataxia telangiectasia mutated (ATM)‐checkpoint kinase 2 (Chk2) branch of DDR in response to RV infection in vitro. We found activation of the transducer kinase ATM and its downstream effector Chk2 in RV‐SA11‐infected cells, the activation response being maximal at 6‐hr post infection. Moreover, ATM activation was found to be dependent on induction of the upstream sensor Mre11‐Rad50‐Nbs1 (MRN) complex. Interestingly, RV‐SA11‐mediated maximal induction of ATM‐Chk2 pathway was revealed to be neither preceded by occurrence of nuclear DNA damage nor transduced to formation of damage‐induced canonical nuclear foci. Subsequent investigations affirmed sequestration of MRN components as well as ATM‐Chk2 proteins away from nucleus into cytosolic RV replication factories (viroplasms). Chemical intervention targeting ATM and Chk2 significantly inhibited fusion and maturation of viroplasms leading to attenuated viral propagation. Cumulatively, the current study describes RV‐mediated activation of a noncanonical ATM‐Chk2 branch of DDR skewed in favour of facilitated viroplasm fusion and productive viral perpetuation.